Investigation of Nonlinear Absorption Coefficient of rGO-Incorporated ZnO: Al Composite Thin Film by Z-Scan Technique - Sreeja, V.G; Rekha, S.; Anila, E.I (Current Research Progress in Physical Science Vol. 9, 2025)
Graphene, a single-layer, two-dimensional nanomaterial, has gained significant attention in various scientific and technological fields due to its remarkable properties. Its exceptional optical, mechanical, thermal, and electronic characteristics make it highly suitable for applications in optoelectronics and photonics. The fabrication of a reduced graphene oxide (rGO)-integrated aluminum-doped zinc oxide (ZnO: Al) composite thin film on a glass substrate using the spin coating technique has been presented. In this study, rGO/ZnO: Al thin films were fabricated on thoroughly cleaned glass substrates using the spin coating technique. Reduced graphene oxide (rGO) was synthesized using a modified Hummer’s method. The influence of rGO on the structural and linear optical characteristics of the rGO/ZnO: Al composite film was examined through X-ray powder diffraction (XRD), Scanning Electron Microscopy (SEM) and UV-Vis absorption spectroscopy. Structural analysis confirmed the presence of a hexagonal wurtzite structure, with strong interfacial bonding between rGO and ZnO: Al. The incorporation of rGO led to a redshift in the band gap energy of ZnO: Al. The nonlinear absorption behavior of the composite thin film was investigated using the open-aperture Z-scan technique with a Q-switched Nd: YAG laser at 532 nm. The Z-scan results revealed that the composite film exhibits reverse saturable absorption, with a nonlinear absorption coefficient (\(β\)) of 5.93 × 10-5 cm/W. The incorporation of rGO leads to a decrease in the ZnO: Al diffraction peak intensity, which can be linked to the reduction of ZnO content in the composite. These findings highlight the potential of rGO/ZnO: Al thin films for applications in absorbing-type optical devices, including optical limiters, optical switches, and optical sensor protection in the field of nonlinear optics. In conclusion, the incorporation of rGO enhances exciton formation in ZnO: Al, leading to improved linear absorption and band gap modulation. Open-aperture Z-scan measurements reveal the presence of reverse saturable absorption (RSA), primarily driven by two-photon absorption (TPA) and free carrier absorption (FCA).